Effect of sodium bicarbonate on gains of stocker cattle fed grain on tall fescue pastures - Brazle, F. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
Adding sodium bicarbonate to the grain supplement of steers grazing lush, low endophyte, tall fescue pasture had no effect on cattle performance.
Keywords: Beef; Sodium bicarbonate; Stocker cattle; Fescue